Application of the SMED method to increase the efficiency of the sealing process in a Peruvian company that produces flexible plastic - Vargas Acha, Jose Alejandro (2022)
Currently, in the Peruvian industrial sector, most companies are affected by the low efficiency provided by the staff when carrying out their respective work. This arises because most companies are looking for the cheapest labor they can get and not all these people have the economic capacity to receive a good level of education. In manufacturing companies, it is almost always possible to observe "the law of minimum effort in the operators" which causes operations without added value to arise in the processes, unnecessary delays and all this translates into processes with low efficiency. What we want to demonstrate in the following investigation is how, with adequate training for the personnel, all these mentioned defects can be reduced and with a not very high investment for the company. There are many tools that we can use that the Lean Six Sigma methodology gives us depending on the objective to improve. This article mentions the implementation of the SMED tool in a flexible plastic production company where we were able to achieve an 8% increase in the efficiency of the sealing area with the reduction of product change over time.